Strategi Guru dalam Meningkatkan Keaktifan Belajar pada Mata Pelajaran Aqidah Akhlak di MA NW Pepao - Nila Aurel; Enda Nanda (Kasta: Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2025)
This study aims to determine the strategies used by teachers in increasing learning activity and what are the supporting factors and inhibiting factors in increasing learning activity in the subject of aqidah akhlak. This type of research is field research with a descriptive qualitative approach method. The research informants used in this study were aqidah akhlak teachers, class XI students and the head of the madrasah. With the technique of determining informants, namely purposive sampling. Data collection techniques using observation, interviews and documentation. Based on the results of the study, the use of teacher strategies in increasing learning activity in the subject of aqidah akhlak is to use direct learning strategies, interactive learning strategies and independent learning strategies. However, this has not run optimally with some students who are still embarrassed to ask or express opinions and make teachers as facilitators in learning so that some students choose to be passive. The supporting factors for learning activity are influenced by the use of appropriate learning strategies, methods and approaches. While the inhibiting factors consist of two factors, namely internal factors, including physical and spiritual health, low motivation and interest in learning and lack of student ability in understanding the lesson. While external factors include inadequate school conditions, the use of inappropriate teaching methods or strategies, poor relationships with teachers and the influence of friends in learning.